Mycorrhizal inoculation and acclimatization of two micropropagated apple rootstocks - Locatelli, Lucir Maria; Lovato, Paulo Emílio (Pesquisa Agropecuaria Brasileira, 2002)
The combination of micropropagation and inoculation with arbuscular mycorrhizal fungi (AMF) can improve the quality of seedling plants produced on a commercial scale. These techniques allow high quality and homogeneous seedling production in a shorter period of time, but they require understanding of the interaction among fungi, plants, substrates, acclimatization and inoculation techniques. A study was performed under controlled conditions to develop procedures to acclimatize and inoculate AMF in two apple (Malus spp.) rootstocks: vigorous strong-rooted Marubakaido and the dwarfing, poorly rooted M.9. Micropropagated plants were treated with indole-butyric acid (5µM), and then transferred to a soil-based substrate for ex -vitro rooting. The AMF were introduced before and after the rooting phase. A mixture of Scutellospora pellucida, two isolates of Glomus etunicatum, and Glomus sp. was utilized. The rooting phase lasted 21 days and plant growth was evaluated after 51 and 81 days under acclimatization conditions, for increase in height, shoot fresh and dry matter, root fresh matter, root-shoot ratio, and mycorrhizal colonization. Mycorrhizal root colonization ranged from 50% to 70% in both rootstocks. The mycorrhizal inoculation had a positive effect on root and shoot growth of Marubakaido rootstock plants, but had a negative effect on growth in M.9 plants.